Operational and Supply Chain Resilience During Geopolitical Disruptions: A Multiple Perspective Analysis - Ji, Shunyu (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2026)
In the last ten years, global supply chains have been affected by numerous geopolitical events. Although there have been many studies focusing on the concept of resilience, firms still reportedly struggle to recover from the impact of disruption caused by geopolitical events. Therefore, this thesis, which consists of three empirical studies, aims to investigate how to achieve operational and supply chain resilience under the impact of disruptive geopolitical events, based on two different perspectives of resilience, namely the engineering perspective and the social-ecological perspective. Prior to inspecting two perspectives of resilience, the first study investigates how different theoretical perspectives are embedded to explain the current body of supply chain resilience knowledge. This study applied the typical systematic literature review method. The findings of the study show which factors affect the relationship between two opposing forces: supply chain disruptions and supply chain resilience. This study shows how relationships among factors such as structural complexity, environmental uncertainty, performance, and capability could be interpreted differently or even divergently based on the theoretical lens applied by studies. From a theoretical perspective, the findings of this study point to how theory could be used more effectively in SCRES studies to make a stronger contribution. It formulates a cohesive conceptual framework grounded in theories used in past supply chain resilience studies and offers suggestions for future empirical research to explore and explain SCRES. The second study draws attention to the engineering perspective of resilience. This study revisits the accumulation of slack resources, a well-known practice for building operational resilience. Adopting the attention-based view, agency theory, and using the panel-data regression method, this study proposes two competing hypotheses to explore how three different types of slack resources, including capacity slack, inventory slack, and financial slack, impacted firms' operational resilience during COVID-19, and how these slack resources were affected by firms' perception of COVID-19-related risks. The findings show that firms with a higher level of risk perception of COVID-19 possessed more capacity slack and financial slack, but only capacity slack enhanced firms' operational resilience during COVID-19, whereas financial slack, conversely, damaged operational resilience. Using the US-China trade war as a research context, the third study focuses on the social-ecological perspective of resilience. Employing institutional theory and the difference-in-differences method, this study investigates whether firms adapt their supply networks to achieve supply network social-ecological resilience under the impact of geopolitical events, based on the level of regulatory distance and perceived political risk. The findings suggest that firms adapt their supply networks in terms of regulatory distance after being exposed to the trade war. Furthermore, the results suggest that the buying firms' perception of political risk negatively moderates the relationship between their exposure to the trade war and the extent of supply network adaptation.
APPROVED